Ultrasound for vascular access in pediatric patients - Schindler, Ehrenfried; Schears, Gregory J.; Hall, Stuart R.; Yamamoto, Tomohiro (Pediatric anesthesia, 2012)
Summary Objectives In pediatric patients vascular access is often more difficult than in adults because of the smaller size of the vessels and the inability of the patient to cooperate without deep sedation or general anesthesia. Therefore Ultrasound has already become an invaluable tool for vascular access, but the full potential of ultrasound has yet to be fully realized. Improvements in image quality and a better understanding of optimal insertion techniques continue to help clinicians safely and efficiently place catheters with fewer complications. Methods and Technique The probes used for the vascular access are mainly linear and convex type. Higher‐ frequency ultrasound provides a vivid image; however, the signals are remarkably attenuated. Therefore, the choice of the probe with appropriate frequency is essential. As blood vessels are relatively easily identified with ultrasound, ultrasound‐guided vascular access does not require as sharp images as ultrasound‐guided nerve block. For pediatric vascular access, the linear probe with 5–15 MHz, 2–5 cm depth is ideal and adequate for almost all cases. Ultrasound‐guided vascular access has two main approaches: ‘long‐axis’ or ‘in‐plane approach’ and ‘short‐axis’ or ‘transverse approach’. The long‐axis approach visualizes the vessel along the insertion pathway and is commonly used to monitor the entire approach of the needle into the vessel. The short‐axis approach is easier to show the positional relationship and depth of target vessels, but it is much harder to follow the needle tip within the tissues. Conclusion The use of ‘real‐time’ ultrasound has been shown to increase first insertion success, reduce access time, have a higher overall success, and reduce arterial puncture. As the technology continues to improve the use of ultrasound will become as ubiquitous as the lines themselves.